Local and landscape effects on the abundance and diversity of soil arthropods in citrus orchards of Malang and Batu, East Java, Indonesia - ITO FERNANDO; FAIZ NASHIRUDDIN MUHAMMAD; RAHMAT FURQONI; M. BAYU MARIO; RETNO DYAH PUSPITARINI; IRISA TRIANTI; MUHAMMAD AKHID SYIB’LI; AKHMAD RIZALI (Society for Indonesian Biodiversity, 2024)
Abstract. Fernando I, Muhammad FN, Furqoni R, Mario MB, Puspitarini RD, Trianti I, Syib’li MA, Rizali A. 2024. Local and landscape effects on the abundance and diversity of soil arthropods in citrus orchards of Malang and Batu, East Java, Indonesia. Biodiversitas 25: 3920-3927. Soil arthropods are crucial for sustaining the balance and function of agroecosystems. This study aimed to assess the diversity and abundance of detritivorous and predatory soil arthropods across various citrus orchards that differ in agroecosystem management practices and landscape composition. The study was conducted in nine citrus orchards from November 2023 to January 2024, with soil arthropod samples collected using Berlese funnels. Analysis of Variance (ANOVA) was used to evaluate the effects of management practices (local effects) on soil arthropod diversity and abundance, while Generalized Linear Model (GLM) analysis was employed to assess the effects of landscape composition (landscape effects) on soil arthropod diversity and abundance. Meanwhile, Analysis of Similarity (ANOSIM) based on the Bray-Curtis index was used to evaluate differences in soil arthropod composition. A total of 1,562 individuals were collected, representing 16 families, 11 orders, and 3 classes. Among the predatory groups, the most abundant family was Laelapidae, while Entomobryidae was the most dominant among detritivores. The diversity of both predatory and detritivorous arthropods was not influenced by variations in management practices. However, the abundance and composition of predatory arthropods were influenced by the frequency of organic fertilizer application, while detritivores were affected by weeding treatments. At the landscape scale, predator abundance positively correlated with the number of natural habitat patches and the area of citrus orchards. In contrast, detritivores were not influenced by landscape variables. This study highlights the critical roles of land management practices and landscape composition in shaping the abundance and diversity of soil arthropods.